ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH MELAKUKAN MERGER STUDI KASUS PT MITRA KELUARGA KARYASEHAT TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rani Rani; Hesti Setiorini (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
This study intends to objectively find out if PT. Mitra Keluarga Karyasehat’s financial performance before and after the merger differed. Current Ratio (CR), Total Asset Turnover (TATO), Debt to Asset Ratio (DAR), Net Profit Margin (NPM), Return on Asset (ROA), and Earning per Share (EPS) are indicators of financial performance. Secondary data are used as part of the data collection process. It covers the years 2016 through 2021. This study is descriptive-quantitative. The analysis of the statistical test, Normality test, and  the paired-sample t-test, were the analytical techniques employed in this work.  The study found that PT Mitra Keluarga Karyasehat Tbk’s fnancial performance is strong. The Current Ratio (CR), (2-tailed) is found to be 0.048 0.05 using the paired-sample t-test, indicating that there was a difference between the Current Ratio before and after the merger. However, there is no difference for the metrics Total Asset Turnover (TATO), Debt to Asset Ratio (DAR), Net Profit Margin (NPM), Return on Asset (ROA), and Earning per Share (EPS) Using a paired-sample t-test, no difference was found.